Seven Modern Plagues and How We Are Causing Them - Walters, Mark Jerome (Island Press/Center for Resource Economics : Imprint: Island Press, 2014)
Every time we sneeze, there seems to be a new form of flu: bird flu, swine flu, Spanish flu, Hong Kong flu, H5N1, and most recently, H5N7. While these diseases appear to emerge from thin air, in fact, human activity is driving them. And the problem is not just flu, but a series of rapidly evolving and dangerous modern plagues. According to veterinarian and journalist Mark Walters, we are contributing to-if not overtly causing-some of the scariest epidemics of our time. Through human stories and cutting-edge science, Walters explores the origins of seven diseases: Mad Cow Disease, HIV/AIDS, Salmonella DT104, Lyme Disease, Hantavirus, West Nile, and new strains of flu. He shows that they originate from manipulation of the environment, from emitting carbon and clear-cutting forests to feeding naturally herbivorous cows "recycled animal protein." Readers will both learn how today's plagues first developed and discover patterns that could help prevent the diseases of tomorrow.